Fast handover and QoS framework for mobility support in heterogeneous networks - Mai, Ngoc Son (2009)
The next generation wireless network is predicted to be a heterogeneous network of various wireless technologies such as: WiFi, WiMAX, Bluetooth, GPRS and UMTS. With these wireless technologies, the Internet users can virtually access the Internet from anywhere and with a number of option; either at home by WiFi or outdoor by WiMAX and UMTS. However, the current network architecture does not support mobile devices to roam freely across networks or in other words, does not have mobility support. A mobile device can not keep its on-going sessions continued while crossing to another network. Besides the standard Mobile IP, Terminal Mobility Support Protocol is another proposal to support application mobility using Session Initiation Protocol. Even though these proposals allow mobile nodes to roam freely across different networks, their poor handover management still poses some problems such as: long handoff delay, high packet loss, lack of QoS provisioning, no efficient support to handoffs between heterogeneous network.